Application of the response surface methodology to determine optimal conditions of castine calcination in a full-scale rotary kiln. Issue 2 (3rd April 2021) - Mbuya, Bienvenu Ilunga; Kime, Méschac-Bill; Kawama, Francis Ngoie; Arad, Susana
ABSTRACT: The optimisation of the calcination process in industrial lime kilns is of particular importance because it affects the final quality of the lime, coal consumption, and pollutant emissions. This work investigated the effects of different operating variables of a full-scale rotary kiln on the minimisation of unburned castine and reactivity of produced lime. The L8 (2 7 ) Plackett-Burman's experimental plan was used for screening the significant variables on the calcination yield and the quality of the lime. Sequentially, Box-Behnken design approach, L15 (3 3 ), under Response Surface Methodology (RSM) was used to determine the best combination of the variables optimising the calcination of castine. Quadratic models were developed to characterise the influence of selected significant variables, temperature of the smoke chamber ( x 1   = 400, 500, and 550°C), kiln rotational speed ( x 2   = 120, 90, and 70 s/revolution) and coal flow rate ( x 4  = 0.5, 0.7, and 1.0 t/h), on the responses obtained. Under optimised conditions, the lime produced yielded 0.93% of unburned castine and a reactivity of 93.96°C, corresponding to the configuration: x 1  = 120, x 2  = 0.5, and x 3  = 550°C. Analysis of variance was conducted to assess the strength of evidence of the developed models. Good correlation coefficients were obtained for unburned castine ( R 2  = 0.92, p  < 0.031) and reactivity ( R 2  = 0.96, p  < 0.006), indicating that the models developed could be used to estimate castine calcination response.